Analisis Kinerja Keuangan Di Tinjau Dari Rasio Profitabilitas Dan Rasio Aktivitas Pada PT. ACE Hardware Indonesia Yang Terdaftar Di Bursa Efek Indonesia - PURWO HERIANTO; ARDI PAMINTO; MUSDALIFAH AZIS (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The purpose of this study was to analyze the financial performance at PT ACE Hardware Indonesia through analysis profitability ratios and activity ratios. The research model is made is through the study observation, namely data collection by viewing documents on the Indonesian stock exchange, analyze financial statements and library research (library research), the research done by using literature and writing - writing that is closely connected with the object writing is intended to gain the theoretical basis that will be used in discussing the issues examined. The results showed that the ratio of the activity has increased, in 2014, while the ratio of profitability decline in 2013 and 2014. Based on the calculation of the financial performance of PT ACE Hardware Indonesia for a period of five years if the terms of the ratio of profitability and activity ratio is less efficient, it is evident that the company failed in the planning and implementation of strategies to increase corporate profits. The Company is unable to evaluate or sustain success in financial performance in the past. This can result in a decrease in the number of customers in the future.Keywords: Profitability Ratios, Activity Ratios and Financial Performance                  Company